2014
DOI: 10.1128/aem.03639-13
|View full text |Cite
|
Sign up to set email alerts
|

Elevated CO 2 and Phosphate Limitation Favor Micromonas pusilla through Stimulated Growth and Reduced Viral Impact

Abstract: bGrowth and viral infection of the marine picoeukaryote Micromonas pusilla was studied under a future-ocean scenario of elevated partial CO 2 (pCO 2 ; 750 atm versus the present-day 370 atm) and simultaneous limitation of phosphorus (P). Independent of the pCO 2 level, the ratios of M. pusilla cellular carbon (C) to nitrogen (N), C:P and N:P, increased with increasing P stress. Furthermore, in the P-limited chemostats at growth rates of 0.32 and 0.97 of the maximum growth rate ( max ), the supply of elevated p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
80
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 75 publications
(87 citation statements)
references
References 63 publications
5
80
1
Order By: Relevance
“…This finding is in line with previous studies, which have shown that picoeukaryotes can benefit 334 strongly from OA in both laboratory and mesocosm studies (Meakin and Wyman, 2011;335 Newbold et al, 2012;Schaum et al, 2012;Brussaard et al, 2013;Maat et al, 2014;Schulz et 336 al., 2017). Such positive response to OA could indicate that picoeukaryotes such as M. pusilla 337 are mainly dependent on diffusive CO 2 supply and thus directly benefit from higher CO 2 338 concentrations Schulz et al, 2013;Schulz et al, 2017).…”
Section: Micromonas Pusilla Benefits From Warming 296supporting
confidence: 89%
See 1 more Smart Citation
“…This finding is in line with previous studies, which have shown that picoeukaryotes can benefit 334 strongly from OA in both laboratory and mesocosm studies (Meakin and Wyman, 2011;335 Newbold et al, 2012;Schaum et al, 2012;Brussaard et al, 2013;Maat et al, 2014;Schulz et 336 al., 2017). Such positive response to OA could indicate that picoeukaryotes such as M. pusilla 337 are mainly dependent on diffusive CO 2 supply and thus directly benefit from higher CO 2 338 concentrations Schulz et al, 2013;Schulz et al, 2017).…”
Section: Micromonas Pusilla Benefits From Warming 296supporting
confidence: 89%
“…Hence, this species can be expected to thrive well under conditions 399 expected for the end of this century (Stocker, 2014), potentially increasing its ecological 400 relevance even further. Regarding the importance of the nutrient availability, laboratory 401 experiments found beneficial OA effects on M. pusilla primary production to persist also under 402 P limitation (Maat et al, 2014), while in a mesocosm community, OA-dependent increases in 403 M. pusilla abundances disappeared when the system ran into P and N co-limitation (Engel et 404 al., 2008). Thus, it remains to be seen how the combined effects of warming and OA manifest 405 under low nutrient conditions.…”
Section: Implications For the Current And Future Arctic Pelagic Ecosymentioning
confidence: 99%
“…The impact of viruses on phytoplankton communities is also related to P-availability as the shortage of this nutrient is assumed to decrease the percentage of lysed cells (Wilson et al, 1996;Monier et al, 2012;Maat et al, 2016a,b). Recently, Maat et al (2014) have evaluated the outcome of P limitation on viral infection in picoeukaryote Micromonas pusilla, reporting a prolongation of the latent period from 6 to 12 h, and an 80% reduction in viral burst sizes compared to P-replete conditions. Phosphorus stress has been pointed out as a strong selective agent, with some phage having in their genome host-like phosphorus assimilation genes that are upregulated when the host is phosphorous starved, thus promoting P acquisition necessary for phage dispersion (Kelly et al, 2013).…”
Section: Viruses and Phytoplankton Mortalitymentioning
confidence: 99%
“…Several studies using phytoplankton host-virus culture systems showed that major nutrient availability influences viral production and see review by Mojica and Brussaard, 2014). For example, phosphorus (P) limitation of the virally infected phytoplankton host results in a prolonged latent period, i.e., the time between infection and the initial release of progeny viruses from the host cell, for the infecting viruses (Maat et al, 2014). Moreover, P-stress resulted in reduced viral burst size, i.e., the number of newly formed viruses released per lysed host cell (Bratbak et al, 1998;Maat et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…For example, phosphorus (P) limitation of the virally infected phytoplankton host results in a prolonged latent period, i.e., the time between infection and the initial release of progeny viruses from the host cell, for the infecting viruses (Maat et al, 2014). Moreover, P-stress resulted in reduced viral burst size, i.e., the number of newly formed viruses released per lysed host cell (Bratbak et al, 1998;Maat et al, 2014). These studies proposed shortage of phosphorus as a viral production substrate as well as possible host energy deficiency as reasons for the lower and delayed viral particle yield.…”
Section: Introductionmentioning
confidence: 99%